2012
DOI: 10.1128/jb.00495-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Third Osmoprotectant Transport System, the OsmU System, in Salmonella enterica

Abstract: The growth of Salmonella enterica serovar Typhimurium mutants lacking the ProP and ProU osmoprotectant transport systems is stimulated by glycine betaine in high-osmolarity media, suggesting that this organism has an additional osmoprotectant transport system. Bioinformatic analysis revealed that the genome of this organism contains a hitherto-unidentified operon, designated osmU, consisting of four genes whose products show high similarity to ABC-type transport systems for osmoprotectants in other bacteria. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…CBS domains are known to control the activity of the ATPase subunit by sensing variations in ionic strength in the cell during osmotic shifts (28)(29)(30), and it has been proposed that CBS domains may be predictors of osmoregulatory activity for the ABC transporter (19,29). The lack of a CBS domain is consistent with emerging data showing that YehZYXW ABC transporters are not involved in resistance to hyperosmotic stress (17,(19)(20)(21), though they share significant sequence similarity to known compatible solute importers.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…CBS domains are known to control the activity of the ATPase subunit by sensing variations in ionic strength in the cell during osmotic shifts (28)(29)(30), and it has been proposed that CBS domains may be predictors of osmoregulatory activity for the ABC transporter (19,29). The lack of a CBS domain is consistent with emerging data showing that YehZYXW ABC transporters are not involved in resistance to hyperosmotic stress (17,(19)(20)(21), though they share significant sequence similarity to known compatible solute importers.…”
Section: Resultssupporting
confidence: 75%
“…The PBP component of the operon (gene locus bab1_0226) is most closely related to Escherichia coli and Salmonella enterica YehZ, which has been described as a component of a putative compatible solute osmoprotectant transport system, YehZYXW (17)(18)(19)(20). The Yeh system is related in primary structure to the glycine betaine OsmU/ ProU uptake systems of S. enterica and E. coli and the OpuB/OpuC choline transporter of Bacillus subtilis (17,(20)(21)(22)(23). However, the function of YehZYXW in vivo remains unclear.…”
mentioning
confidence: 99%
“…The hypervirulence phenotype of the ⌬metQ strain, which is defective in the transport of methionine, may be metabolically connected with the intracellular polyamine imbalance caused by ⌬potD. YehZ shows high sequence homology with OsmX, which is the osmoprotectant-binding protein of the OsmU transport system (45,59). It was recently found that Salmonella strains lacking OsmU stimulate trehalose accumulation and thereby become resistant to intracellular stressors, such as oxidative stress and acidic pH (45).…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria are often equipped with at least two uptake systems for substances with crucial physiological roles; these systems can possess different affinities, capacities, specificities, and regulation mechanisms to satisfy different physiological needs in the changing environment (48). As for aromatic amino acids, more than one uptake system was demonstrated to exist in C. glutamicum (28).…”
Section: Discussionmentioning
confidence: 99%